ANALISIS BATASAN PRAKTIK TAKZIM MENURUT PERSPEKTIF HADIS DI LINGKUNGAN PESANTREN RUBATH ADZ-DZIKRA LIL MU’MININ TEMBUNG PASAR 9 MEDAN: ANTARA FEODALISME DAN TAKZIM - Sayyid Naufal Ibrahim Tanjung; Agusman Damanik (DIRAYAH : Jurnal Ilmu Hadis, 2026)
Takzim (reverence) is a common practice in pesantren (Islamic boarding schools) and is considered sacred when interacting with teachers. However, the diverse ways in which students (santri) express takzim have sparked public debate due to the lack of a clear boundary between genuine respect and individual cultism. Therefore, this study aims to delineate the boundary between reasonable and excessive takzim. Utilizing a qualitative approach, this field research was conducted at the Rubath Adz-Dzikra Lil Mu'minin Pesantren. The findings indicate that the analysis of takzim boundaries focuses on two prevalent practices at the institution: standing to welcome someone's arrival and bowing as a form of respect. The study reveals a divergence between the principles of Islamic education and modern education regarding the perception of teachers. Consequently, takzim practices within pesantren may be misconstrued as improper when viewed through the lens of modern educational philosophy. The results show differing scholarly opinions regarding bowing out of respect; some scholars deem it makruh (reprehensible), while others permit it provided it does not emulate the ruku' (bowing) position in prayer. Meanwhile, regarding standing to welcome someone, scholars agree that the practice is permissible, provided it does not foster arrogance or riya' (ostentation) in the individual being welcomed.